The European rescue of the nation-state - Milward, Alan S. (Routledge, 2000)
"For the second edition of this classic economic and political account of the origins of the European Community Alan Milward has completely revised and updated the chapter on the United Kingdom. On one level the book is an original analysis of the forces which brought the EC together, on another it is an explanation based on historical analysis of the future relationship between nation-state and the European Union. Combining political with economic analysis, and based on extensive primary research in several countries, it offers a challenging interpretation of the history of the western European state and European integration."--Jacket